Las concesiones viales y la consulta previa: caso Ruta del Sol tramo 3 (2016)
The main objective of this work is to determine the regulatory process following the concession, considering the process of prior consultation should be developing road projects that require environmental license, which have as a component performing prior consultation as well is required within the concessioned route. Highway concession and infrastructure development in Colombia, implementation of prior consultation on road infrastructure: As contextualization to the development of this work the historical development of two key issues for this, namely observed.